"Biosimilar, so it looks alike, but what does it mean?" A qualitative study of Danish patients' perceptions of biosimilars. Issue 5 (15th March 2022) - Varma, Meera; Almarsdóttir, Anna Birna; Druedahl, Louise C.
Abstract: Biosimilars are highly similar follow‐on products for biologics that can foster biologics competition. Questionnaire studies have attempted to gauge the patient perspective on biosimilars, but none have delved deeper into how patients view biologics and switching of these. Considering Denmark has one of the highest biosimilar uptakes worldwide, the aim of this study was to investigate how Danish patients with psoriasis, arthritic diseases or inflammatory bowel disease perceive biosimilars. Twelve participants were semi‐structurally interviewed in either a focus group or an internet‐based, individual interview between May 2019 and July 2019. Content analysis was inductively applied. Participants on originators voiced more reluctance towards using biosimilars than those already using them. Both participants using originator and biosimilar products expressed concerns about reoccurrence of disease symptoms due to differences in effectiveness and safety. Participants generally struggled with understanding biosimilarity, and they voiced a need to be well‐informed about switching. They were all aware of and accepted how healthcare budget restrictions played a role in the push to use biosimilars. To improve biosimilar uptake and willingness to switch to a biosimilar, patient‐centred information on efficacy and safety and explanation of the societal benefits of the savings from using biosimilars must be carefully communicated.